Vortioxetine vs. Other Antidepressants in Patients with Major Depressive Episode With or Without Substance Use Disorder - Kotzalidis, Georgios D.; Lombardozzi, Ginevra; Matrone, Marta; Amici, Emanuela; Perrini, Filippo; Cuomo, Ilaria; De Filippis, Sergio (Current Neuropharmacology, 2021)
Background: Major Depressive Episodes (MDEs) may characterise many psychiatric disorders. Its pharmacotherapy is laid with unmet needs, rendering the testing of new drugs necessary. Objective: To compare the effects of vortioxetine with those of other antidepressants (OADs) in a 1-year naturalistic setting. Methods: We included 126 adult patients with anMDE in the course of major depressive (MDD), bipolar (BD), or schizophrenia spectrum disorders (SSOPDs), with or without substance use disorder (SUD), who received 5-20 mg/day oral vortioxetine, and compared them with 100 patients receiving OADs at baseline and after 1, 3, 8, and 12 months on their scores on the MADRS, the CGIS, the 24-item BPRS, the YMRS, the Hamilton Anxiety Rating Scale, a Visual Analogue Scale for craving, the Columbia-Suicide Severity Rating Scale, and the WHOQOL-BREF. Results: Patients on vortioxetine improved similarly to those on OADs on all measures, independently from having or not a comorbid SUD. However, they improved with time better than their OADcounterparts if affected by BD or SSOPDs, but not MDD, on the CGI-S, BPRS depression, anxiety, and manic symptoms. SUD hampered the response of anxiety to treatment. Men improved on depression with time better than women. Conclusion: MDEs responded to vortioxetine similarly to OADs by improving in depression, general psychopathology, anxiety, suicidal thinking, and quality-of-life, independently from SUD comorbidity. MDEs of patients with BD or SSOPDs on vortioxetine responded better than that of patients on OADs. Clinical Trial Registration No. 17354N.
Keywords: Schizophrenia Spectrum and Other Psychotic Disorders